North American Migrants Working as Tour Guides in Alamos in Mexico Mobilities and Imaginaries - Clausen, Helene Balslev (Diálogos Latinoamericanos, 2013)
The article focuses on the guide’s narratives and practices when guiding “House Tours” that is the most visited tourist attraction in the Mexican town. We argue that these guides provide narratives about concrete imaginaries that constitute not only authenticity but also utopia – that we consider one of the core elements in tourism imaginaries. The guides inscribe themselves in the utopian imaginaries in the Western hemisphere that continue to be essential in the socio-cultural and political construction of society. We conclude that these tourism imaginaries of places (and people) cannot be considered only as commoditized representations with a symbolic content. Alamos displays that way the significant connections that exist in terms of both representations and mobilities.